Trend Mortalitas dengan Indikator Gross Death Rate dan Net Death Rate Per Tahun di Rumah Sakit PKU Muhammadiyah Surakarta Tahun 2017-2021 - Bangkit Ary Pratama (Indonesian Journal on Medical Science, 2023)
The mortality rate at the PKU Muhammadiyah Surakarta Hospital in 2017-2021 has fluctuated. Trend calculations were needed to predict the increase or decrease in GDR and NDR values ??to assist hospital management in making decisions. The purpose of this study was to determine the annual trend of GDR and NDR at PKU Muhammadiyah Surakarta Hospital in 2017-2021. This type of research was descriptive with a retrospective research design with a total sample from the entire population, namely the recapitulation of the daily census of hospitalizations per year 2017-2021 with univariate analysis, the method of data collection was the observation method. Based on the results of observations and calculations, it was found that the GDR value was still below the set national standard limit of <4.5% and fluctuated every year in 2017-2021 respectively 2.06%, 2.28%, 2.16% , 3.63%, 3.51%. While the NDR value has increased every year but is still below the set national standard limit of <2.5%, the NDR value in 2017-2021 was 1.22%, 1.53%, 1.54 respectively %, 2.03%, 1.97%. The conclusion of the research is that the trend of GDR and NDR at PKU Muhammadiyah Surakarta Hospital in 2017-2021 tends to increase. The GDR in 2017 trended 1.87 to 3.59% for the 2022-2024 forecast the numbers were 4.02, 4.45 and 4.88, while the NDR trended 1.26 increased to 2.06 and the estimates are 2.26, 2.46, and 2.66.